Pengaruh Digital Marketing terhadap Minat Beli Produk Skincare Lokal di Kecamatan Belopa - Mursyid Mursyid; Bunga Julita (Journal of Institution and Sharia Finance, 2023)
This study aims to examine how customers' inclination to purchase local skincare products is affected by social media marketing and electronic word-of-mouth. The major objective of this study is to ascertain whether electronic word-of-mouth and social media marketing significantly affect local skincare consumers' propensity to buy items, either individually or collectively. Quantitative research is used, and measures are made using a Liker scale. The population in this study are users of local skincare products in Belopa District with an undetermined population size. 100 respondents made up the sample, which was selected using a straightforward random sampling method and the Lemeshow algorithm. By handing out questionnaires and disseminating them online and in person, survey data was collected. SPSS is used for data processing and analysis methods 24 program tools. The findings of this study demonstrate that there is a significant simultaneous influence between electronic word of mouth and social media marketing on buying interest in local skincare, with a T_count value of 5.331 > T_table 1.985, a partially significant influence of social media marketing on buying interest in local skincare, and a T_count sig value of 5.183 > T_table 1.985.